Implementation Of IoT In Improving The Efficiency Of Hostage Release Operations With The QHBM Method - Dekki Widiatmoko; Kasiyanto Kasiyanto; Mokhammad Syafaat (ITEGAM-JETIA, 2024)
In an increasingly complex security context, hostage release operations require innovative strategies to improve efficiency and safety. This article discusses the application of Internet of Things (IoT) technology and the Queen Honey Bee Migration (QHBM) method in improving the effectiveness of these operations. Conventional methods often face drawbacks, such as a lack of direct monitoring and limited communication. This study proposes the use of QHBM algorithms for optimizing troop deployment and resource allocation based on real-time data from IoT. This study uses quantitative and simulation approaches to evaluate the effectiveness of QHBM in the management of rescue operations. The results of the analysis show that QHBM is more efficient in energy consumption and bandwidth usage, reducing energy consumption by up to 10% compared to conventional methods. QHBM also shows improved connectivity stability with stronger signals at more distant nodes. With these optimizations, QHBM successfully extends the life of battery-based devices and supports more nodes without network congestion. These findings show that the application of QHBM in IoT resource management can improve communication quality and operational efficiency, providing practical guidance for professionals in the military, law enforcement, and crisis management.